Hemoglobinuria in the Early Poststem-Cell–Transplant Period: Risk Factors and Association with Outcomes. Issue 10 (28th October 2021) - Kompotiatis, Panagiotis; Manohar, Sandhya; Alkhateeb, Hassan B.; Hogan, William J.; Nath, Karl A.; Leung, Nelson
Visual Abstract: Abstract : Key Points: Post-HSCT hemoglobinuria was associated with graft type (BMT+Cord). Post-HSCT hemoglobinuria was associated with early (48–72 hours) post-HSCT AKI. Graft type (BMT+Cord) was associated with AKI among patients with hemoglobinuria. Background: Information on risk factors of hemoglobinuria after hematopoietic stem-cell transplant (HSCT) and its association with AKI, mortality, and engraftment is limited. Methods: We conducted a retrospective cohort study on all consecutive adults that underwent HSCT from January 6, 1999, to November 6, 2017. The study included 6039 patients that underwent bone marrow transplantation (BMT), umbilical cord blood, and peripheral blood stem-cell transplantation (PBSCT). Results: Early post-HSCT, AKI occurred in 393 (7%) patients, and 52 (0.9%) patients had post-HSCT hemoglobinuria. Post-HSCT hemoglobinuria was associated with graft type (BMT+Cord), underlying disease (lymphoma, acute leukemia), and fludarabine-based conditioning regimen. Post-HSCT hemoglobinuria was associated with early (48–72 hours) post-HSCT AKI. Graft type (BMT+Cord) was associated with AKI among patients with hemoglobinuria. AKI in patients with hemoglobinuria was associated with delayed platelet engraftment and delayed WBC engraftment but not 100-day mortality. Conclusion: Close monitoring is recommended in this patient group to facilitate a good engraftment outcome.